Sickness Absence and Local Benefit Cultures - Assar Lindbeck; Mårten Palme; Mats Persson (Research Institute of Industrial Economics (IFN), 2014)
In many countries, sickness absence financed by generous insurance benefits is an important concern in the policy debate. There are strong variations in absence behavior among local geographical areas. Such variations are difficult to explain in terms of observable socioeconomic factors. In this paper, we investigate whether such variations are related to group effects in the form of social interaction among individuals within neighborhoods. Well-known methodological problems arise when trying to answer this question. A special feature of our efforts to deal with these problems is that we adopt several alternative approaches to identify group effects. Our study is based on a rich set of Swedish panel data, and we find indications of group effects in each of our approaches.
Keywords: H56; I38; J22; Z13; 330; Income insurance; Sic-pay; Social norms; Neighborhood Effects; Sickness Absence